Effective Antimicrobial Activity of Plectasin-Derived Antimicrobial Peptides against Staphylococcus aureus Infection in Mammary Glands - Li, Lianbin; Wang, Liangliang; Gao, Yuqi; Wang, Jianhua; Zhao, Xin (Frontiers in Microbiology, 2017)
Staphylococcus aureus (S. aureus) is the causative agent for a wide variety of illnesses ranging from minor skin infections to life-threatening diseases. Development of antibiotic resistance by the bacteria has rendered many antibiotics ineffective. It has been known that plectasin-derived antimicrobial peptides (NZ2114 and MP1102) are promising alternatives to antibiotics. However, their activities against S. aureus in mammary glands were unknown. Our objective was to assess the antimicrobial activities of NZ2114 and MP1102 against S. aureus in milk, in cultured mammary epithelial cells, and in a mouse model in order to evaluate their potentials as anti-mastitis agents. NZ2114 and MP1102 showed in vitro bactericidal effects against S. aureus both in the culture medium and milk. NZ2114 and MP1102 at the concentration of 100μg/mL reduced the number of S. aureus by almost 100% within 4h in processed bovine milk. Similarly, both NZ2114 and MP1102 were efficient to reduce the number of internalized S. aureus in cultured mammary epithelial cells. Finally, both antimicrobial peptides significantly reduced the S. aureus load and concentrations of TNF-α and IL-6 in mammary glands, compared to a buffer control in the mouse model. Our results suggest that NZ2114 and MP1102 may be used to treat S. aureus -induced mastitis.